A Collaborative Online International Learning (COIL) Experience in Early Childhood Teacher Education - Kristin Severinsen Spieler; Randi Engtrø; Lovise Lohne Pedersen; Anne Karin Vikstøl Olsen (Education Sciences)
This study explores the use of Collaborative Online International Learning (COIL) as a pedagogical method to enhance intercultural competence among Early Childhood Teacher Education (ECTE) students, with an emphasis on Indigenous perspectives in Norway and Canada. Using qualitative focus group interviews with Norwegian students engaged in a COIL project with Canadian peers, this research identifies key pedagogical benefits and logistical considerations of this approach. The findings indicate that COIL enhances critical intercultural skills, such as cross-cultural communication and collaboration. This study highlights the necessity of establishing clear guidelines and objectives from the beginning, alongside active teacher participation, to foster a supportive environment that builds student confidence and autonomy. Additionally, COIL has broadened students’ understanding of cultural perspectives, which is valuable for their application in early childhood education settings. Ultimately, this study positions COIL as a valuable method for promoting intercultural collaboration and embedding Indigenous perspectives. This approach serves as a form of internationalization at home, preparing students to integrate diverse cultural insights into their professional roles in Early Childhood Education and Care.